Gambaran kepatuhan lansia dalam pencegahan penularan Covid-19: Studi Kualitatif - Anindya Arum Cempaka; Maria Theresia Arie Lilyana (JURNAL NERS LENTERA, 2024)
Introduction: Most of the world's population is elderly. Older people are a vulnerable group during the Covid-19 period. An older adult will experience decreased cognitive abilities, physiological functions, physical fitness and body immunity. Older adults with chronic or comorbid illnesses are significantly more susceptible than others. Purpose: This study aims to explore the description of elderly compliance in preventing transmission of Covid-19 so that it brings benefits, especially in the field of nursing, so that it can improve the quality of life of older people in the future. Research method: This qualitative study with Colaizzi data analysis involving 10 participants in Surabaya. Results: In-depth interviews conducted with respondents resulted in 4 themes, namely: 1) Health protocols followed by older adults; 2) Sources of information on how to prevent transmission; 3) Factors supporting transmission prevention measures. Conclusion: Education and training programs regarding disease prevention strategies, the long effects of covid, and how to distinguish between hoaxes and valid information from the internet are highly recommended.Keywords: elderly; prevention of transmission; covid-19